ISOLASI DAN IDENTIFIKASI BAKTERI PENGHASIL PROTEASE YANG DISKRINING DARI TERASI - ARFARITA, NOVI (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2015)
Terasi is a traditional fermented shrimp paste of Indonesia popularly used as an important ingredient in many Indonesian cuisines, and further screened for their protease-producing bacteria. A total of 117 bacterial isolates were retrieved from 4 terasi samples. When inoculatedusing skim milk agar, 71 isolates ( 61%) produced distinct clear zones implying their proteolytic activity. A bacterial isolate namely Bacillus S2-3 wasselected for further study due to its widest clear zones when thebacterial cells and culture supernatant were used. This strain could grow up to 60oC with a broad pH range of 5 – 9. The optimal growth condition was at pH 6 and 37oC. The enzyme activity was also characterized using azocasein method. The optimal pH of bacterialenzymes was between 6 and 7 whereas the optimal temperature of BacillusS2-3 proteases was 22 – 24oC. For thermostability, the S2-3 enzymes remained active up to 2h at 40 and 50oC. The results ofbiochemical tests, BacillusS2-3 was identified as Bacillussubtilis, later explored it is potential for the purposes for food industry